Harmonic Load Mitigation Using the Optimal Double Tuned Passive Filter Technique - Muhammad Murtadha Othman; W Muhammad Faizol bin W Mustapha; Amirul Asyraf Mohd Kamaruzaman; Aainaa Mohd Arriffin; Ismail Musirin; Nur Ashida Salim; Zulkiffli Abdul Hamid; Nofri Yenita Dahlan (Institute of Advanced Engineering and Science, 2017)
Harmonic is one of the power quality disturbances customarily imminent in an unbalanced electrical system. Harmonic represents as the multiple integral of fundamental frequency of voltage and current inflicting towards the shifting in system frequency causing to a disruptive operation of electrical devices. This paper investigates on the performance of passive filter intrinsically by utilizing the inductor and capacitor electrical components to mitigate harmonic problem emanating from an unbalanced electrical system. In particular, explication in this paper will focus on the optimal parameters specification for the double tuned passive filter that used to overcome the phenomenon of harmonic issue. The two case studies constituting with different number of harmonic orders injected in a system were introduced to distinguish effectiveness of double tuned passive filter in solving the aforesaid problems. The parameters configuration of the passive filter are automatically tuned by the MATLAB® software to reduce the total harmonic distortion incurred in a system designed under the Simulink® software.